A modified model to estimate the screening current-induced magnetic field of a REBCO magnet. (1st April 2022) - Tang, Yunkai; Liu, Donghui; Li, Dongke; Yong, Huadong; Zhou, Youhe
Abstract: Experiments have shown that the actual value of the magnetic field in a magnet wound by rare-earth (RE) Ba2 Cu3 O7− x tape during operation is less than its design value due to the effect of the screening current-induced magnetic field (SCMF). Several simulation methods have been used to calculate the SCMF. In this paper, a modified model is proposed to estimate the SCMF of a magnet based on the previous simple model. The inductance correction and field-dependent critical current density are considered in the modified model. Two parameters, the reversal and Nagaoka coefficients, are introduced in the model. The former is used to track the location of the minimum SCMF value in the charging process and the latter is applied to correct the induction of the magnet. The numerical results indicate that the SCMF estimated by the modified model is in agreement with those from experiments and the finite element method. Moreover, the effects of electromagnetic and geometrical parameters on the reversal and Nagaoka coefficients are also investigated. Finally, the model is extended to estimate the SCMF of a no-insulation magnet.